Health Problems of Under-five Children in a Rural Area of Mymensingh District, Bangladesh - Hossain, Md Tufael; Dipu, Sultana Sobnam (Community Based Medical Journal, 2022)
A cross-sectional, descriptive study was conducted to determine health problems of under-five children in a selected rural area of Mymensingh District in Bangladesh. This study was done on the background that the document about community prevalence of health problems of under-five children is scarce though it has public health importance. This was a community-based cross-sectional descriptive study conducted among 144 children belonging from birth to 5 years residing in Churkhai village of Bhavokhali union, Mymensingh Sadar Upazila in between November and December of 2019, as a part of Residential Field Site Training of 3rd year students of Community Based Medical College, Bangladesh (CBMC,B). A purposive sampling technique was adopted. A pre-designed, pre-tested questionnaire has been used to collect required information by face-to-face interviewing mothers of under-five children. The data were entered and analyzed by SPSS version 20.0. Respondent mothers ranged from 16 years to 45 years, mean age 25.47±5.332 years. Majority of mothers were literate (75.69%), housewife (91.67%), belonged to middle class (69.44%). Out of total 144 children ranging from birth to 59 months, mean age 29.83±19.54 months, male: female ratio was 97.26:100. Majority of children (50.69%) were healthy. Nutritional status was assessed by history taking (history of birth weight) weight, height measurement and clinical examination. Prevalence of low birth weight was 15.28%. Prevalence of under-nutrition was 16.67% and over-nutrition was 1.39%. On clinical examination, prevalence of anemia was found 4.17%. The leading health problem was nutritional 22.22%, followed by respiratory illness 12.50%, diarrhoea 7.64%, skin disease 4.17%, dental caries 0.69%, conjunctivitis 0.69%, acute suppurative otitis media 0.69%, accidental injury 0.69%. Most of the family had safe water supply (98.61%), sanitary latrines (85.42%), semi-pucca house (50%) and suffer air pollution 69.44%. The nutritional profile was quite similar, but disease situation was better than the results of other studies in Bangladesh and in other developing countries. CBMJ 2022 January: vol. 11 no. 01 P: 27-32